PTU-061 Vitamin D Deficiency is Widely Prevalent in South Asian Patients with Inflammatory Bowel Disease. (4th June 2013) - Boyd, C; Limdi, J K
Abstract : Introduction: There has been resurgent interest in recent years in the pro-hormone vitamin D in its role and plausible effects on immune regulation and inflammatory bowel disease (IBD). We postulated a wide prevalence of vitamin D deficiency in South Asian patients with implications for the control of their IBD. The aim of our study was to review vitamin D assessment in a South Asian IBD cohort. Methods: We conducted a retrospective review of 102 South Asian patients attending IBD clinics in our institution. Clinical data including demographics, disease characteristics (Montreal classification) and therapy were obtained from electronic record review. Serum 25-hydroxyvitamin D (25-OHD) concentrations were recorded in all patients tested and in all having serial measurements. Results: Of 106 patients reviewed, 55 were male. The median age was 38 years (range 16–80) and mean disease duration was 9.5 years. Seventy-six patients had ulcerative colitis (UC) and 30 had Crohn's disease (CD). Five patients were current or ex smokers (4.7%). Vitamin D status was assessed in 52 patients (49%), 26 had serial measurements. Median 25-OHD was 10.25 (range 3.3–44.4). Fifty one patients had levels < 25 ng/ml consistent with deficiency and all 52 had insufficient levels < 50 ng/ml. Of the patients with deficiency 35 had UC and 16 had CD. Of the UC patients, 18 had pancolitis, 13 had left sided disease and 4 proctitis. Of the CD patients 5 had penetrating disease and 4 had stricturing disease. Forty-three of the deficient patients had received steroids and 29 received immunomodulatory therapy (27 azathioprine, 3 methotrexate, 1 cyclosporin, 2 6MP, 10 infliximab, 6 adalimumab). Seven deficient patients (4 CD, 3 UC) required a colectomy and the mean 25-OHD level in this group was 10.7 (range 4.0–20.1 ng/ml). Mean time to surgery was 3.6 years (range 0–8 years). Of the CD patients 1 had a subtotal colectomy, 3 had hemicolectomy and of the UC patients 2 had subtotal colectomy and 1 had total colectomy. Conclusion: There was a high prevalence of Vitamin D deficiency although assessment was suboptimal and probably reflective of a wider experience. Patients with vitamin D deficiency appeared to have a more aggressive disease course. The role of vitamin D in IBD is a science in evolution underpinning exciting implications for research. Meanwhile vitamin D deficiency is under-recognised and consequently undertreated with likely implications for adequate disease control in this potentially vulnerable group. Disclosure of Interest: None Declared